(untitled) (Research, Society and Development, 2023)
The objective of this work was to evaluate the flow of nitrous oxide (N2O) in exclusive cropping systems with eucalyptus (CEE) and integration-animal-forest system (IPF). The work was developed at the Chapada Grande Farm in Regeneração-PI, where two soil management systems (CEE and IPF) were selected to evaluate N2O emissions. Gas samples were collected using static chambers and daily and accumulated emissions were calculated. The mean N2O fluxes found in the CEE and IPF systems were low during the evaluation, with negative values ​​indicating the consumption of this gas in the soil. In the CEE, the highest emission peak was observed at the beginning of the evaluation, while in the IPF, the highest peak was observed at the end. These variations in the two systems under study are due to rainfall events occurring during the evaluation period. In general, the IPF emissions were higher than those observed in the CEE. This can be attributed to the effects of soil compaction caused by the presence of animals during grazing, as well as by the release of waste products such as feces and urine. These animals. Regarding the accumulated emissions of N2O over the evaluation period, the values ​​are low in both systems, but in the IPF the emissions were higher. The N2O emissions in the two evaluated systems are mainly associated with rainfall events. The IPF system is less efficient in relation to eucalyptus cultivation in the mitigation of greenhouse gases like N2O.